Subtype and gender-differentiated burden of stroke in China (1990–2021): attributable risk factors and future projections based on the Global Burden of Disease Study 2021 - Wang, Qi; Xu, Jiachun; Zhang, Jingxin; Tan, Jing; Wang, Ziqi; Wang, Dongjun; Zhou, Zhen (Frontiers in Nutrition, 2025)
IntroductionUsing data from the Global Burden of Disease Study 2021 (GBD 2021), this study analyzed the 32-year trends (1990–2021) of stroke burden in China, quantified the attributable risk factors, and projected the future trajectories (2022–2035) of stroke and its subtypes. It also emphasized subtype- and gender-specific disparities to provide evidence for precision prevention.MethodsAge-standardized incidence rate (ASIR), prevalence rate (ASPR), mortality rate (ASMR), and disability-adjusted life years rate (ASDR) of stroke were analyzed using estimated annual percentage change (EAPC) and Joinpoint regression. The population attributable fraction (PAF) was used to quantify the burden of stroke-related disability-adjusted life years (DALYs) attributed to risk factors, and Bayesian age-period-cohort (BAPC) modeling was applied to project future burden.ResultsIn 2021, the ASIR, ASPR, ASMR, and ASDR of stroke in China were 204.75, 1301.42, 138.03, and 2,648.02 per 100,000 populations, respectively. From 1990 to 2021, ASMR (EAPC = −1.92; 95% CI: −2.17 to −1.67) and ASDR (EAPC = −2.05; 95% CI: −2.25 to −1.86) of stroke decreased, while ASPR increased (EAPC = 0.34; 95% CI: 0.31 to 0.38). Subtype analysis showed opposing trends: IS ASIR (EAPC = 0.94; 95% CI: 0.88 to 1.00) and ASPR (EAPC = 1.02; 95% CI: 0.96 to 1.08) increased, whereas ICH and SAH burdens decreased (ICH ASIR EAPC = −2.24; SAH ASIR EAPC = −3.70). Males had higher ASRs than females in 2021, except for ICH ASPR. High systolic blood pressure (PAF = 56.04%), ambient particulate matter pollution (PAF = 24.37%), and smoking (PAF = 17.91%) were the top three risk factors for stroke-related DALYs; high LDL cholesterol (PAF = 28.42%) ranked second for IS. Projections indicated that by 2035, overall stroke ASIR (from 208.27 to 194.07 per 100,000) and ASMR (from 139.94 to 100.34 per 100,000) would decrease, but IS ASIR would rise to 156.44 per 100,000 (from 139.98 per 100,000 in 2022).ConclusionsThe stroke burden in China shows a downward trend, with a subtype-specific feature of increasing IS and decreasing ICH/SAH. High systolic blood pressure is the potential risk factor for stroke, with variations across subtypes and genders. Targeted interventions such as smoking control for males, sodium intake reduction for females, and LDL cholesterol management for IS, are urgently needed to mitigate the future IS burden.